All‐Inorganic Transparent Composite Materials for Optical Limiting. Issue 10 (17th February 2020) - Feng, Xu; Shi, Zhuo; Chen, Jiejie; Yu, Tao; Jiang, Xiaofang; Du, Guanxin; Qiu, Jianrong; Zhou, Shifeng
Abstract: Nonlinear optical limiting, which enables dynamic radiation filtration, has important implications for photonics, medicine, and advanced manufacturing. A major challenge is the scalable fabrication of all‐inorganic materials with good stability, high optical quality, and excellent optical limiting performance. Herein, a topological engineering strategy is presented for constructing all‐inorganic composite titanate glass with robust performance in optical radiation control. Notably, the rational control of the topological configuration of highly polarized species and their local organization leads to the considerable enhancement of two‐photon absorption coefficients (≈7 times). Mechanical response can also be improved with an estimated elastic modulus and hardness of 10.5 and 115.4 GPa, respectively. This improvement allows the creation of novel all‐inorganic composite materials with excellent ability for dynamic optical radiation filtration. Results suggest that the proposed topological engineering strategy for constructing titanate glass can be extended to other highly polarized glass systems to develop a new generation of nonlinear photonic materials. Abstract : A new strategy for designing and fabricating photonic glass for the considerable improvement of its nonlinear optical response is proposed. The conceptually novel and universal fabrication methodology based on topological engineering and compositing is highly effective for producing all‐inorganic optical limiting function.